Prion protein interaction with soil humic substances: environmental implications. - Gabriele Giachin (PLoS ONE, 2014)
Transmissible spongiform encephalopathies (TSE) are fatal neurodegenerative disorders caused by prions. Animal TSE include scrapie in sheep and goats, and chronic wasting disease (CWD) in cervids. Effective management of scrapie in many parts of the world, and of CWD in North American deer population is complicated by the persistence of prions in the environment. After shedding from diseased animals, prions persist in soil, withstanding biotic and abiotic degradation. As soil is a complex, multi-component system of both mineral and organic components, it is important to understand which soil compounds may interact with prions and thus contribute to disease transmission. Several studies have investigated the role of different soil minerals in prion adsorption and infectivity; we focused our attention on the interaction of soil organic components, the humic substances (HS), with recombinant prion protein (recPrP) material. We evaluated the kinetics of recPrP adsorption, providing a structural and biochemical characterization of chemical adducts using different experimental approaches. Here we show that HS act as potent anti-prion agents in prion infected neuronal cells and in the amyloid seeding assays: HS adsorb both recPrP and prions, thus sequestering them from the prion replication process. We interpreted our findings as highly relevant from an environmental point of view, as the adsorption of prions in HS may affect their availability and consequently hinder the environmental transmission of prion diseases in ruminants.